Hypoxia regulates epithelial to mesenchymal transition-associated genes in human trophoblast cells by modulating DNA methylation - Jaganmoy Choudhury; Bodhana Dhole; Kanika Aggarwal; Palak Singh; Moses Azaraiah Jala; Deepak Pandey; Pradeep Kumar Chaturvedi; Surabhi Gupta (PLoS ONE, 2026)
Successful pregnancy is dependent on an aptly developed and functional placenta. During placentation, epithelial cytotrophoblast cells (CTBs) transdifferentiate into migratory extravillous trophoblasts (EVTs) that invade the maternal endometrium. Improper differentiation can result in inadequate EVT invasion leading to placental malformation-related pathologies like preeclampsia. Acquisition of invasive phenotype by EVTs indicates the involvement of epithelial to mesenchymal transition (EMT). In the early-stage placenta, the trophoblast cells are exposed to a hypoxic environment. However, the regulation of EMT in trophoblasts by this hypoxic condition is unclear. Therefore, we analyzed the expression pattern of EMT-associated genes and their DNA methylation level in two different trophoblast cell lines grown under hypoxia. Exposure to hypoxia was confirmed by a significant increase in the expression of HIF1A target gene Carbonic Anhydrase 9. Modulated expression of some EMT-associated core genes indicated the induction of EMT in trophoblasts by hypoxia. Interestingly, a significant increase in the expression of MMP2 and MMP9 was observed in HTR8/SVneo cells but not in JEG-3 cells. In HTR8/SVneo cells, hypoxia-induced modulation in the methylation levels of promoters for E-Cadherin and MMP9 gene correlated well with alterations in their gene expression. The expression of TET1, a DNA demethylating enzyme, also increased after hypoxia exposure. Thus, we concluded that hypoxia changes expression and promoter methylation of some EMT-associated genes in trophoblast cells.